Religious Micro-celebrity: Young Preachers’ Self-Presentation in Digital Sphere - Afidah, Ida; Kurniati, Nia; Nasir, Malki Ahmad; Muttaqin, Ahmad (UIN Antasari Banjarmasin, 2024)
This article analyzes young Muslim preachers’ self-presentation in the digital sphere, especially on the Instagram platform. This attempts to answer how and why self-branding has become so prevalent among young Indonesian Muslim preachers on Instagram. Using self-presentation theory, this qualitative study argues that young Muslim preachers’ self-presentation is as strategy to become micro-selebrity in digital sphere. The existence of various features on Instagram makes it easier for preachers to self-expression, self-record, and recognition. Young preachers as Instagram users become micro-celebrity because they always want recognition and to be the center of social interaction. They are actively involved with followers, being the center of attention, active in selfies, inserting jokes, and posting daily activities as strategies to be closer to digital natives. Surprisingly, their posts are not dominated by activities related to religious rituals. On the contrary, the more natural the self-presentation is presented by the young preachers, or the more similar the interests and characters of the audience are, the easier the self-branding will be. This article also theoretically implies that young Muslim preachers are themselves a brand and self-presentation is a form of brand management to become religious micro-celebrities.